2019
DOI: 10.3389/fimmu.2019.01420
|View full text |Cite
|
Sign up to set email alerts
|

Complex Bacterial Consortia Reprogram the Colitogenic Activity of Enterococcus faecalis in a Gnotobiotic Mouse Model of Chronic, Immune-Mediated Colitis

Abstract: Inflammatory bowel diseases (IBD) are associated with compositional and functional changes of the intestinal microbiota, but specific contributions of individual bacteria to chronic intestinal inflammation remain unclear. Enterococcus faecalis is a resident member of the human intestinal core microbiota that has been linked to the pathogenesis of IBD and induces chronic colitis in susceptible monoassociated IL-10-deficient (IL-10 −/− ) mice. In this study, we chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 82 publications
0
48
0
Order By: Relevance
“…The context within which individual microbes colonize a host can alter their function. For example, immunomodulatory properties of individual strains can be altered in an inflamed host or when cocolonized with different organisms (20,22). Thus, the immune landscape of the gut is influenced by the presence of specific strains and the compositional context of the broader microbiota, making the rational design of therapies targeting the microbiota challenging.…”
Section: Significancementioning
confidence: 99%
“…The context within which individual microbes colonize a host can alter their function. For example, immunomodulatory properties of individual strains can be altered in an inflamed host or when cocolonized with different organisms (20,22). Thus, the immune landscape of the gut is influenced by the presence of specific strains and the compositional context of the broader microbiota, making the rational design of therapies targeting the microbiota challenging.…”
Section: Significancementioning
confidence: 99%
“…Likewise, Lengfelder et al in Dirk Haller's group further demonstrated the importance of evaluating the pathogenic potential of a single microbial isolate not only via monoassociation of gnotobiotic mice but also as part of a complex bacterial consortia (88). They used E. faecalis, an organism shown to induce intestinal inflammation in monoassociated colitis-prone IL-10 −/− mice, to examine the functional role of this bacterium within the inflammatory response and as a member of a complex bacterial community.…”
Section: Studying Bacterial Genes Involved In Aggressive Functionmentioning
confidence: 99%
“…The context within which individual microbes colonize a host can alter their function. For example, immunomodulatory properties of individual strains can be altered in an inflamed host, or when co-colonized with different organisms (Lengfelder et al 2019;Yang et al 2019). Thus, the immune landscape of the gut is influenced by the presence of specific strains and the compositional context of the broader microbiota, making the rational design of therapies targeting the microbiota challenging.…”
Section: Introductionmentioning
confidence: 99%